2014
DOI: 10.1097/ccm.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

Extent, Risk Factors, and Outcome of Fluid Overload After Pediatric Heart Surgery*

Abstract: Fluid overload occurs early after cardiac surgery and is associated with prolonged PICU length of stay and ventilation. Future fluid overload avoidance trials may confirm or refute a true fluid overload-outcome causative association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 33 publications
6
69
0
4
Order By: Relevance
“…FO had been previously found to be associated with increased risk of mortality in pediatric patients [12,13,25,26,28,30,31]. To our knowledge, only one study verified the use of early FO as a predictive marker in the pediatric population.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…FO had been previously found to be associated with increased risk of mortality in pediatric patients [12,13,25,26,28,30,31]. To our knowledge, only one study verified the use of early FO as a predictive marker in the pediatric population.…”
Section: Discussionmentioning
confidence: 59%
“…Thirty-seven children were excluded: 4 died and 5 were discharged from PICU in the first 24 h after admission, 4 were transferred to another hospital or unexpectedly discharged due to economic reasons, and 24 had incomplete data on fluid balance. There were no significant differences between the included and excluded patients in age (median [IQR]: 11 vs. 14 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] months; p=0.300), gender (male/female 238:132 vs. 23/14; p=0.849), and PRISM III score (3 [0-6] vs. 2.5 [0-11.5]; p=0.621).…”
Section: Patient Characteristicsmentioning
confidence: 93%
See 1 more Smart Citation
“…13 E n n i ñ o s , s e m o s t r ó q u e e l balance acumulado de las primeras 72 horas se asociaba a más días de ARM en pacientes con lesión pulmonar aguda 14,15 y en aquellos e n p o s o p e r a t o r i o d e c i r u g í a cardiovascular. 16 También se evidenció que un balance acumulado mayor del 15% del peso corporal se asociaba a un deterioro en la oxigenación y prolongación de ARM. 17 L o q u e e s t e e s t u d i o i n t e n t a comprobar es si la asociación entre balance de fluidos y prolongación de ARM se puede establecer con datos correspondientes a las primeras 48 horas de comenzada la ventilación mecánica y no se limita a un subgrupo de pacientes.…”
Section: Introductionunclassified
“…13 In children, it was shown that the balance accumulated in the first 72 hours was associated with more days on AMV in patients with acute lung injury 14,15 and in those in the cardiovascular postoperative period. 16 A cumulative balance higher than 15% of the body weight was demonstrated to be associated with impaired oxygenation and prolonged AMV. 17 What this study is trying to demonstrate is if the association between fluid balance and prolonged AMV can be established with data corresponding to the first 48 hours of having started mechanical ventilation and is not limited to a subset of patients.…”
Section: Introductionmentioning
confidence: 99%